2013
DOI: 10.1093/bja/aes465
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of surgical patients with undiagnosed obstructive sleep apnoea

Abstract: We found that anaesthetists and surgeons failed to identify a significant number of patients with pre-existing OSA and symptomatic undiagnosed OSA, before operation. This study may provide an impetus for more diligent case finding of OSA before operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
111
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 260 publications
(117 citation statements)
references
References 34 publications
1
111
0
5
Order By: Relevance
“…OSA is defined by a pause in breathing that lasts at least 10 seconds and a decrease in oxygen saturation by 4% from the patient's baseline oxygen saturation (Henrichs & Walsh, 2012;Mehta et al, 2014;Singh et al, 2013). The obstructive breathing pattern characteristic of OSA occurs when the muscles that typically support an open airway during sleep, relax in tone causing the airway to collapse and airflow to decrease or cease altogether (Henrichs & Walsh, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…OSA is defined by a pause in breathing that lasts at least 10 seconds and a decrease in oxygen saturation by 4% from the patient's baseline oxygen saturation (Henrichs & Walsh, 2012;Mehta et al, 2014;Singh et al, 2013). The obstructive breathing pattern characteristic of OSA occurs when the muscles that typically support an open airway during sleep, relax in tone causing the airway to collapse and airflow to decrease or cease altogether (Henrichs & Walsh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The obstructive breathing pattern characteristic of OSA occurs when the muscles that typically support an open airway during sleep, relax in tone causing the airway to collapse and airflow to decrease or cease altogether (Henrichs & Walsh, 2012). OSA is a potentially fatal disease process and has been independently associated with higher rates of morbidity and mortality as well as increased perioperative complications, including a higher incidence of difficult intubation, obstructive breathing, postoperative complications, and increased length of hospital stays (Mehta et al, 2014; Singh et al, 2013). A recent meta-analysis found that OSA was associated with a higher risk of postoperative cardiac events, respiratory failure, and intensive care unit (ICU) admission (Kaw et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations